(untitled) (Dhaka University Journal of Science, 2015)
In this paper, an algorithm and its computer oriented program have been developed for solving transportation programming (TP) reducing it into a linear program (LP). After formulating it into linear programming problems the number of variables becomes large. It then, becomes more difficult and time-consuming if it is done manually with simplex method. By using the computer program the solution can be found in a shorter time. It will be shown that a TP with a large number of variables can be solved in few seconds by using this method. A number of numerical examples are presented to demonstrate the method developed in this research. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21758 Dhaka Univ. J. Sci. 63(1): 1-7, 2015 (January)